Animals in the Prophetic World: Literary Reflections on Numbers 22 and 1 Kings 13 - Way, Kenneth C. 1993- (2009)
In this article, the stories of Balaam’s donkey (num. 22.22-35) and the man of God from Judah (1 Kgs 13) are analyzed independently and are also compared for similarities. Features that are common to both accounts include: the importance of the word of YHWH, the employment of animals as literary characters, the motif of death, and the portrayal of animals as divine agents. This study argues that the literary function of animals as divine agents is a distinctive characteristic of the so-called preclassical phase of biblical prophecy.
Keywords: preclassical prophecy; Lion; Donkey; Balaam; Animals